STRATEGI UMAT BERAGAMA DALAM MODERASI BERAGAMA - Sopi Ananda; Melly; Sriliza (Adisam Publisher, 2026)
Religious moderation is a crucial concept in maintaining social harmony amid religious and cultural diversity. This study aims to analyze the strategies employed by religious communities in implementing the values of religious moderation based on a literature review. The research adopts a qualitative approach using a library research method by examining and analyzing various written sources, including books, scholarly journals, and official documents relevant to the theme of religious moderation. Data analysis techniques involve data collection, data reduction, data presentation, and drawing conclusions through a descriptive-analytical approach. The findings indicate that strategies for strengthening religious moderation can be realized through enhancing inclusive and contextual religious understanding, promoting interfaith dialogue, strengthening the role of educational institutions and religious leaders, and internalizing the values of tolerance and social justice in social life. This study emphasizes that a literature-based approach is effective in formulating a conceptual framework for religious moderation that can serve as a foundation for strengthening policies and practices that support harmonious religious life.